An overview of ethical concerns in re-engineering the human body - Syed, Bilal Shah; Hussain, Mahmud; Yusof Khan, Zarinah Jan; Sayed, Inayatullah Shah (Scholars Middle East Publishers, 2017)
Today, the tremendous possibilities that arise with scientific advancements in medicine, biotechnology, and affiliated sciences are distinct and clear. And so are the abuses, negative implications, and ethical dilemmas that arise with such revolutionary technology. As a civilized global society, it is our responsibility to ensure that such achievements may not be marred by the negligent actions of a few. The potential of gene modification technology is very exciting indeed, but we need to advance with caution for the sake of the safety of our global community. The aim of this article is to highlight the current practices and experimentations being conducted in the field of genetic engineering, the laws or the lack of laws pertaining to genetic engineering, the ethical concerns that arise from dwelling into such experiments and the Islamic perspective on this issue. This study reached to the conclusion that the status quo restricts scientists from conducting unauthorised experiments based on a voluntary moratorium. There should be well defined boundaries that do not create unethical issues while at the same time promote research in this field which has the potential to cure diseases and improve the well-being of humankind.